The Relationship between Professional Behavior and Organizational Commitment of Nurses in Ilam Province of Iran - Mojgan Mohammadimehr; Sanaz Zargar Balaye Jame; Saeed Sheikhi; Dariush Rahmati (Tehran University of Medical Sciences, 2017)
Background and Aim: Organizational commitment is one of the important elements in improving the quality of services and nursing job. Since, the professional behavior is one of the most important variables in organization success, the present study was designed with the aim of determination of  relationship between nurseschr('39') professional behavior and organizational commitment.  Materials and Methods: This was a cross sectional and descriptiveanalytical study. Research statistical society included all nurses in Abdanan, Darehshahar, and Dehloran in Ilam Province of Iran (N=198). Hundred and thirty one people were selected using Cochranechr('39')s formula and random sampling. Data was collected via professional behavior questionnaire and organizational commitement questionnaire. Data was analyzed via descriptive and analytical statistics.  Results: The result of Pearson correlation test showed that there was a positive and significant relationship between professional behavior and organizational commitement (p<0/01=, r=0/558). Also there were positive and significant relationships between professional behavior and nurseschr('39') emotional commitement (p<0/01, r=0/435), nurseschr('39') continuous commitement (p<0/01, r=0/506) and nurseschr('39') normative commitement (p<0/01, r=0/519).  Conclusion: There was a significant relationship between professional behavior and organizational commitement of nurses. Therefore, we suggest that hospital executives and policymakers provide appropriate situation for improving the variables of nursing professional behavior.